(untitled) (CONTINUIDAD Y DISCONTINUIDAD EN EL ESPACIO IBEROAMERICANO, 2026)
Lately, the question has been raised as to what extent editors and/or publishers influence the final product of the work of translators or cultural mediators and, consequently, whether the mediators are responsible for the published translation. It is clear that it is normally the mediator who chooses a strategy according to which they intend to carry out their work and, therefore, particularly with respect to cultural elements, they can opt, among other techniques, for foreignization or domestication. However, once the translation is submitted, mediators often lose control over the translated text, which is then handled by editors and/or publishers, who rarely know the source language in which the work is written. Therefore, their interventions can result in an incoherent, sometimes even erroneous translation, and can be reduced to a common denominator: paratranslation.